Водные и прибрежные полужесткокрылые (Hemiptera-Heteroptera) Кавказского заповедника - Пучкова, Л.В. (Вестник зоологии, 1968)
A review is given of the species composition and distribution according to biotopes of 16 species of the water and coastal Hemiptera — Heteroptera found out in the highlands of the western part of the main Caucasus ridge.